Four keys to unlock IgG - Nimmerjahn, Falk; Ravetch, Jeffrey V. (Journal of Experimental Medicine, 2021)
The identification of discrete subclasses within the immunoglobulin G (IgG) isotype by Grey and Kunkel (1964. J. Exp. Med. https://doi.org/10.1084/jem.120.2.253) provided the framework for our current understanding of differential IgG subclass activity in protective and self-reactive immune responses.
CRIS-Team Scopus Importer:2021-03-26